Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.